Presence of nhe, cytK, and ces in Bacillus cereus isolated from dairy products commercially available in Brazil - Reis, André Luiz Souza; Pereira, Juliano Gonçalves [UNESP]; Montanhini, Maike Tais Maziero; Bittencourt, Juliana Vitória Messias; de Almeida Nogueira Pinto, José Paes [UNESP]; dos Santos Bersot, Luciano (My University, 2019)
The aim of this study was to evaluate the presence of genes (nheABC, cytK, and ces) among bacteria present in dairy products (100 pasteurized milk, 110 UHT milk, and 50 powdered milk). In total, 63 Bacillus cereus isolates were tested and subjected to the detection of genes by using PCR. Regardless of the type of sample analyzed, the most frequent were nheC (82.5%), cytK (68.2%), and nheA (66.6%). The genes nheB and ces were detected in only 23.8% and 3.1% of the isolates, respectively. None of the isolates presented the three genes simultaneously. The combination of nheABC-cytK was highly prevalent in most of the isolates, present in 25% from pasteurized milk and 20% of those from powdered milk. None of the cultures showed nheABC and ces simultaneously, and the combination of cytK-ces was found in only one isolate from pasteurized milk (2.7%) and one isolate in powdered milk (6.6%). These results demonstrate the presence of B. cereus toxin genes in dairy products from Brazil. Practical applications: Consumption of food contaminated with Bacillus cereus is a risk to public health as this micro-organism produces diarrheal and emetics toxins. Thus, studies that aim to research genes that code for these toxins can be important tools for dairy industries to establishment of process parameters, limits and actions to control of contamination. This article demonstrated that strains of B. cereus isolated from milk and dairy products may contain genes encoding the toxins (nhe, cytK, and ces), so the risk of food poisoning should not be neglected.